Human-Computer Systems Interaction Backgrounds and Applications 4 - Hippe, Zdzisław S.; Kulikowski, Juliusz L.; Mroczek, Teresa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents a fascinating, state-of-the-art collection of papers on the recent advances in human-computer systems interaction (H-CSI). It offers a detailed description of the status quo in the H-CSI field and also provides a solid base for further development and research in the area. The content is divided into three parts: I. Aid systems for disabled people; II. Decision-making support systems; and III. Information and communication systems.  It is intended for a wide audience of readers who are not necessarily experts in computer science, machine learning or knowledge engineering, but are interested in human-computer systems interaction, and the combination of general and specific papers offers readers deeper insights than might be gleaned from research papers or talks at conferences. It touches on all the current hot topics in the field of H-CSI.
Imperceptible Sensor Infrastructure for rule-Based Active Safety Prevention in the Household -- A Tactile Pen and the Presentation of Texture Sensation with a Visual Display -- Direction of Echo Arrival Estimation by Indirect Determination  of Phase Shift -- Visual and Auditory Attention Stimulator for Assisting Pedagogical Therapy -- Usefulness of Keystroke Dynamics Features in User Authentication and Emotion Recognition -- A Discrete Dynamic System Approach to Studying Project Management Processes Using the General Theory of Linear Max Plus Systems -- Sparsely Synchronized Distributed/Parallel Genetic Algorithm for Road Traffic Network Division -- Decision Method Choice in a Human Posture Recognition Context -- TFD-Based Dynamic Resource Reservations for SD and HD Video Transmission over a Multiservice Network.
Keywords: Computational intelligence; Artificial intelligence; User interfaces (Computer systems).; Human-computer interaction; Computational Intelligence; Artificial Intelligence; User Interfaces and Human Computer Interaction